Numerical and experimental investigation of (de)lithiation-induced strains in bicontinuous silicon-coated nickel inverse opal anodes. (1st April 2016) - Cho, Hoon-Hwe; Glazer, Matthew P.B.; Xu, Qian; Han, Heung Nam; Dunand, David C.
Abstract: A volume expansion of up to ∼310% occurs upon the lithiation of silicon in Si-coated nickel inverse opal anodes, which causes (de)lithiation-induced mismatch stresses and strains between the Si and Ni during battery cyclical (dis)charging. These (de)lithiation-induced mismatch strains and stresses are modeled via sequentially coupled diffusion- and stress-based finite element (FE) analysis, which takes the mechanical contact between the Si and Ni phases into account, as well as the complex geometry and material properties of the Si-coated Ni inverse opal anode system. During lithiation, compressive strains up to 0.2% are developed in the Ni scaffold since the Si active layer expands. A rapid recovery of these lithiation-induced mismatch strains occurs during subsequent delithiation, though full recovery is not achieved. Strain histories upon multiple (de)lithiation cycles vary with the choice of various mechanical contact conditions employed between the two phases, since the mechanical contact properties determine how the contacted phases interact mechanically. The numerically predicted strains are compared with experimental strain data collected in operando using X-ray diffraction. The simulated strain histories agree with the measured data, enabling the possibility of predicting mechanical performance and eventual degradation using only numerical modeling. In particular, the FE model indicates that plastic deformation occurs first in the lithiated Si active layer, then in the Ni scaffold. Graphical abstract: